Control y automatización de una procesadora de café en el cantón Catamayo. - Castillo Paz, Henry Luis (2005)
At the present time the technology advances very quickly, demanding that the industries are modernized, what implies that this is a matter of current interest. This thesis work this focused to the application of a control system and automation, in the Planta Process of Coffee in the Cantón Catamayo. The same one that could be integrated easily to a system (ESCADA). We also use the PACS which have a system that unites the characteristics of a PLC and of a PC, that which contributes to that she/he has bigger covering of possibilities and it is also but robust that the FieldPoint Reason why in this work you development a control program and automation by means of a system SCADA(Supervisory Control and Acquisition Dates), using software (LabVIEW) that associates different variables of the process where by means of screens, functions, it allows monitor ear the different variables of the same one, and also help to the taking of decisions in its control. To end she/he made a study of the costs that implies the elaboration and construction of this project. The same one that you development to contribute with the advance and technological development of the County and of the Country.